Strategi Adaptasi Masyarakat di Permukiman Sekitar Bantaran Rel Kereta Api Kecamatan Gondokusuman Yogyakarta - Dhanty Prihatiningsih; Deva Foster Haroldas Swasto (REKA RUANG, 2021)
The settlements along the railway tracks are illegal settlements. The settlement is located in an area that is not intended as a developable area. The existence of the illegal settlement may cause several urban problems. Yogyakarta is one of the major cities in Indonesia and is experiencing rapid population growth. The population growth has encouraged informal settlement growth, especially for the low and middle-income population. One of the growing informal settlements in Yogyakarta is the settlement along the railway tracks in Gondokusuman District. This slum area has been inhabited since fifty years ago. The experience of living in the informal settlement has made the inhabitants build an adaptive strategy to survive in the slum area. This research was conducted to study the adaptive strategy of the slum dwellers in the settlement along the railway tracks in Gondokusuman District. This research utilizes the qualitative-inductive approach to understand the formation and the choice of the adaptation strategy of the slum dwellers in the study area. This research reveals that there are three main strategies practiced by the slum dwellers, which are (1) individual adaptation, (2) settlement adaptation, and (3) communal adaptation. The utilization of those strategies has made the slum dwellers survive in the slum area along the railway tracks.